Autophagy activation prevents sevoflurane-induced neurotoxicity in H4 human neuroglioma cells - Zhou You-fa; Wang Qing-xia; Zhou Hai-yan; Chen Gang (Acta Pharmacologica Sinica, 2017)
Aim: The inhaled anesthetic sevoflurane may induce cognitive impairment in both animals and humans. Previous study has shown that sevoflurane triggers ER stress and may lead to apoptosis in rat hippocampal neurons. In this study, we examined whether sevoflurane caused autophagy and its contributions to sevoflurane induced neuronal cell injury. Methods: H4 human neuroglioma cells were exposed to 4.1% sevoflurane for 6 h. Cell viability and apoptosis ratio were assessed using a CCK8 kit and flow cytometry, respectively. Autophagosomes in the cells were detected using GFP-LC3 plasmid transfection or transmission electronic microscopy. The expression of LC3B, p62/SQSTM, C/EBP homologous protein (CHOP) and glucose-related protein 78 (GRP78) was assessed with Western blotting. Results: Sevoflurane treatment induced apoptosis and markedly increased the LC3-II level and GFP-LC3 puncta number, decreased p62 expression in H4 cells. Activation of autophagy by rapamycin (1 μmol/L) significantly reduced sevoflurane-induced apoptosis and increased cell viability, whereas inhibition of autophagy with 3-MA (5 mmol/L) caused the opposite effects. Furthermore, sevoflurane treatment markedly increased the expression of CHOP and GRP78, two hallmark proteins of ER stress. Inhibition of ER stress by 4-phenylbutyrate (500 μmol/L) abrogated sevoflurane-induced autophagy and apoptosis, and improved the viability. Moreover, sevoflurane-stimulated expression of CHOP and GRP78 was inhibited by rapamycin, but further enhanced by 3-MA. Conclusion: Sevoflurane treatment induces ER stress and activates autophagy, which antagonizes sevoflurane-induced apoptosis in H4 human neuroglioma cells. The results suggest that autophagy may be a potential therapeutic target in preventing sevoflurane-induced neurotoxicity.